Avaliação de métodos parasitológicos, imunológicos e moleculares no diagnóstico da esquistossomose mansoni em indivíduos com baixa carga parasitária, antes e após intervenção terapêutica - Fernanda do Carmo Magalhães (2019)
The public policy regarding the control of schistosomiasis in Brazil is based on early diagnosis and treatment; surveillance and control of intermediate hosts; health educational actions and sanitation actions to modify the home and environmental conditions favorable to transmission. Treatment of individuals diagnosed as positive by the standard parasitological method, Kato-Katz, resulted in a significant reduction in morbidity and mortality, but did not interrupt its transmission in endemic areas. To achieve this goal, the refinement of diagnostic methods is needed in order to properly identify individuals with low parasite loads. Thus, this work evaluated the performance of Kato-Katz (KK), Saline Gradient (GRAD), Helmintex® (HTX), urine rapid test (POC-CCA®), ELISA, and RT-PCR methods, in comparison with the herein established reference test, for the diagnosis of schistosomiasis in an endemic area with low parasite load. The reference standard test included all positive individuals detected by at least one direct parasitological method. A cross-sectional study was conducted by collecting three stool samples, one urine sample, and one blood sample from individuals residents from the Brejo do Amparo district, Januária, MG. For KK, 14 slides were prepared from the first stool sample, and two slides from the second and third samples each. The study included 257 individuals, comprised of 122 males (47.5%) and 135 females (52.5%). Their age varied from two to 88 years old, with a mean age of 34.9 years old (SD ± 22.6), and a median of 32 years old (interquartile range from 15 to 51 years). The study population showed to have low income and education level, with 90% of individuals receiving below two minimum wages, and almost 80% having completed elementary school only. The main source of drinking water is the local stream (60% of households), and domestic sewage is not treated. The prevalence of infection defined by the Reference Test was 45.9%, while the KK analysis with two slides identified only 20.4% as positive. KK test sensitivity increased when analyzing a larger number of slides per sample (56.4% with 6 slides, 95% CI 47.0-5.9) or a larger number of stool samples/individual (65.8% with three consecutive samples, 95% CI 56.4-74.0). HTX presented a prevalence of 39.3% and 83.9% (95% CI 74.5-88.9) sensitivity. Although POC-CCA® detected a high prevalence (47.4%) of schistosomiasis mansoni; it presented itself as a technique with low diagnostic concordance. IgG1 anti-SWAP and IgG4 anti-SEA were the best performing immunoglobulins among the isotypes evaluated for diagnosis of S. mansoni in areas of low parasite load, with sensitivity of 62.4% and 73.9%; specificity of 81.2% and 67.3%, and kappa of 0.38 and 0.41, respectively. The RT-PCR was the technique that presented the best efficiency to identify infected individuals; prevalence 54.4% and sensitivity 91.3% (95% CI 84.2 - 95.3). Of the treated infected individuals 97.2% were cured after 30 days. Using the combination of parasitological diagnostic techniques, 4.6%, 13.0% e 21.3% reinfection rates were identified at three, six and 12 months post-treatment. In all situations, 2 KK slides did not allow identification of cured or reinfected patients. In the new epidemiological context of schistosomiasis in Brazil, it is necessary to use a combination of diagnostic techniques, thus increasing the sensitivity in detecting positive individuals with low parasitic burden in endemic areas. The data obtained here will allow the proposition of complementary strategies to control the transmission and eradication of schistosomiasis with the reality of the disease and the performance of the health system. Keywords: schistosomiasis, Schistosoma mansoni, diagnosis, low parasitic load